Investigation of Sociodemographic Characteristics and Results of Recurrent Suicide Attempts: Sample of Ankara Province - Kabadayı Şahin, Esra; Şan, İshak; Bekgöz, Burak; Albay, Burhan (The Bulletin of Legal Medicine, 2022)
Objective: Suicide re-attempt is one of the strongest predictive factors of completed suicide. The aim of this study was to evaluate the socio-demographic data and the results of repeated suicide attempts in the 112-command center of Emergency Services.Methods: The socio-demographic characteristics related to suicide attempts of the patients aged 15 and over applied to the Ankara 112 command center of Emergency Services for recurrent suicide attempts between 2017-2019 were examined through electronic records.Results: There were 8231 applications due to suicide attempts in three years in Ankara province and 847 of them (10.3%) were recorded as recurrent suicide attempts. A total of 344 people who attempted recurrent suicide were 62.5% male and 37.5% female. The vast majority of those who had recurrent suicide attempts were found to have attempted suicide twice (79.9%). The rate of completed suicide among recurrent suicide attempts was 1.5%, all of them were the result of the second suicide attempt. The most common suicide attempt method was drug and chemical use in both sexes, and the most common methods used in completed suicides were firearms and medication/chemical use. According to the seasons, days or hours there was no statistically significant difference between genders or suicide attempts and completed suicides.Conclusion: This is the first study that reports the socio-demographic characteristics of recurrent suicide attempts in our country. In addition to the interventions to recurrent suicide attempts, it is also important to develop preventive and protective strategies for high-risk groups vulnerable to making first suicide attempts.
Keywords: suicide; recurrent suicide attempt; risk factors